2008
DOI: 10.1038/sj.bmt.1705986
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a DNAemia cutoff for preemptive therapy of cytomegalovirus infection in adult hematopoietic stem cell transplant recipients

Abstract: A randomized trial comparing a DNAemia cutoff of 10 000 copies per ml whole blood and first pp65 antigenemia positivity for initiation of preemptive therapy of human cytomegalovirus (HCMV) infection in adult hematopoietic stem cell transplant recipients was completed. DNAemia was chosen for cutoff definition since it is more automatable and standardizable than antigenemia, and more closely reflects the actual viral replication. The primary end point of the study was to compare the number of patients treated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 25 publications
2
37
0
1
Order By: Relevance
“…Nevertheless, there are scarce published data as to how both strategies compare in terms of their clinical efficacy. [2][3][4][5] Although the criteria for initiation and cessation of pre-emptive antiviral therapy guided by the AG assay are rather standard across transplantation centers, there are no consensus criteria as to how active CMV infection should be managed in the QRT-PCR era. 1 In fact, no validated CMV DNA load threshold (in either whole blood or plasma) exists for the inception of antiviral therapy, nor has a consensus been reached as to when antiviral treatment should be stopped (first negative QRT-PCR result/second negative QRT-PCR result/decrease of CMV DNA load below the cutoff for initiation of pre-emptive antiviral therapy).…”
mentioning
confidence: 99%
“…Nevertheless, there are scarce published data as to how both strategies compare in terms of their clinical efficacy. [2][3][4][5] Although the criteria for initiation and cessation of pre-emptive antiviral therapy guided by the AG assay are rather standard across transplantation centers, there are no consensus criteria as to how active CMV infection should be managed in the QRT-PCR era. 1 In fact, no validated CMV DNA load threshold (in either whole blood or plasma) exists for the inception of antiviral therapy, nor has a consensus been reached as to when antiviral treatment should be stopped (first negative QRT-PCR result/second negative QRT-PCR result/decrease of CMV DNA load below the cutoff for initiation of pre-emptive antiviral therapy).…”
mentioning
confidence: 99%
“…Previous studies have shown that high HCMV DNA in whole blood is associated with the development of HCMV infection [34]. HCMV is an important factor for morbidity and long-term outcome after allo-HSCT [35]. It has also been reported that immunosuppression related to allo-HSCT affects HCMV reactivation in the oral cavity [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…This technique offers some advantages over others PCR methods, including increased precision, accuracy, reproducibility and a shorter turnaround time. To date, the clinical utility of using the RT-PCR test to guide preemptive therapy in transplant recipients has been mainly studied in SCT recipients Boeckh M, 2009;Gerna et al, 2008;Gimeno et al, 2008;Harrington et al, 2007;Kalpoe et al, 2004;Lilleri et al, 2004;Limaye et al, 2001;Machida et al, 2000;Ruell et al, 2007;Verkruyse et al, 2006). However, it has not been established a cutoff threshold for initiating antiviral therapy against CMV probably due to the significant differences between the different techniques used to determine the CMV viral load.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have assessed the performance between the different CMV viral load assays available. However, no many studies have compared the differences between the DNA extraction methods used (Fahle & Fischer, 2000;Caliendo et al, 2007;Kalpoe et al, 2004;Leruez-Ville et al, 2003;Boeckh et al, 2009;Gerna et al, 2008;Gimeno et al, 2008). Although during the DNA extraction the majority of the methods use internal controls as a measurement of the DNA loss during the extraction procedure, in the downstream amplification not many of the assays use DNA standards that will facilitate the comparison among the different kits and standardization of the results between hospitals.…”
Section: Introductionmentioning
confidence: 99%